English Language Teaching in Indonesia: A Continuous Challenge in Education and Cultural Diversity - M. Marcellino (TEFLIN Journal: A publication on the teaching and learning of English, 2008)
The linguistic situations and conditions in Indonesia are quite complex by their own natures as more than seven hundred vernaculars with their various dialects from a great number of ethnic groups have been used as media of communication in the country.ÃÂ  Accordingly, the success of English teaching in Indonesia cannot be freed from the students cultural backgrounds, values, customs, and beliefs as well as the political standpoint of the government regarding this foreign language. English language teaching has then undergone more than four changes in its curriculum since the countrys independence and brought no significant impact upon the learning outcomes. This study reveals the substantial unconstructive influence of the students cultures and the non-conducive language environment affecting their language acquisition.ÃÂ  Other aspects related to the teachers performance and class preparations equally contribute to the ineffective classroom interactions.ÃÂ  This study offers some practical suggestions to cope with those problems.